The Creation of the Arabic Version of the Hyperhidrosis Quality of Life Index (HidroQoL©) with Validation and Cross-Cultural Adaptation - Almuhaideb QA; AbuDujain NM; Alghamdi KM (Clinical, Cosmetic and Investigational Dermatology)
Qais A Almuhaideb,1 Nasser M AbuDujain,2 Khalid M Alghamdi3,4 1Department of Dermatology, King Faisal Specialist Hospital & Research Centre, Riyadh, Saudi Arabia; 2Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4Vitiligo Research Chair, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid M Alghamdi, Department of Dermatology, Vitiligo Research Chair, College of Medicine, King Saud University, P.O. Box 240997, Riyadh, 11322, Saudi Arabia, Email kmgderm@gmail.comPurpose: Hyperhidrosis (HH) is characterized by excessive sweating, which can significantly affect quality of life. The Hyperhidrosis Quality of Life Index (HidroQoL©) is the latest tool that has been developed and validated for assessing the quality of life of patients with HH. Because of the absence of an Arabic version of the HidroQoL©, this research aimed to create, validate, and adapt the HidroQoL© into Arabic.Patients and Methods: A quantitative, analytical, cross-sectional study was conducted with HH patients followed up in dermatology or thoracic surgery clinics. We assessed the results reliability through internal consistency and reproducibility by assessing test‒retest reliability. For validity, we conducted an exploratory factor analysis with an interitem correlation matrix and a rotated component matrix.Results: A total of 167 participants were enrolled in this study; 61.1% were males, and 92.8% were Saudi. All 18 items of the HidroQoL©, including the daily life activities domain, psychosocial life domain, and whole HidroQoL©, had Cronbach’s alpha values above 0.7. The test–retest reliability assessment demonstrated strong reproducibility. The correlations between each item and the other 17 items of the scale were positive, ranging between 0.2 and 0.6, and the results of the components analysis suggested that the questionnaire has three domains. The correlation between the test–retest results of the HidroQoL© revealed a significant strong positive correlation (r=0.9, P˂0.001).Conclusion: Our findings revealed excellent psychometric properties of the Arabic HidroQoL© in terms of structural and construct validity, internal consistency, and reproducibility. Proper utilization of the Arabic HidroQoL© adequately assesses the quality of life of those affected by HH.Keywords: perspiration, excessive sweating, validation, Arabic, Saudi Arabia